Urgensi Peningkatan Kompetensi Guru Madrasah Ibtidaiyah: Studi Analisis Tantangan Di Esocial Society Era 5.0 - Barudin; Mulyadi (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2023)
The purpose of this writing is to find out the urgency of increasing the competence of madrasah ibtidaiyah teachers in facing challenges in the era 5.0 social society. The method used uses a descriptive qualitative approach with a field research method (field reseach). There are four competencies that teachers have, namely pedagogical, personality, social and professional competencies accompanied by mastery of technology and digital information. The urgency of improving the competence of madrasah ibtidaiyah teachers is needed and must be improved in facing challenges in the era 5.0 esocial society through supervision activities, teacher performance appraisals, training, workshops, and sustainable teacher competency development. So that the role of teachers is needed which is not found in technology, namely direct interaction in the classroom, emotional bonds between teachers and students, instilling character and role models of madrasah ibtidaiyah teachers.